2014
DOI: 10.1007/s10067-014-2819-4
|View full text |Cite
|
Sign up to set email alerts
|

Association of abnormal lipid spectrum with the disease activity of Takayasu arteritis

Abstract: Our study aimed to determine whether proatherogenic lipid profiles exist in patients with active Takayasu arteritis (TA) and assess the relationship between different lipid profiles and disease activity in TA. A total of 132 premenopausal female patients with TA and 100 sex-, age-, and body mass index-matched healthy controls were included in our study. The clinical data were collected in detail from all participants. Patients with active TA had significantly lower levels of apolipoprotein A1 (apoA1) (1.47 ± 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
4
9
0
Order By: Relevance
“…Some adult TA patients showed dyslipidemia, which may be a risk factor for complicating atherosclerosis [22]. Also, dyslipidemia is suggestive of disease activity [23]. Here, dyslipidemia was identified in 60% (3/5) of cases, similar to that reported previously [22]; however, the disease activity scores for children with and without dyslipidemia were not statistically different.…”
Section: Discussionsupporting
confidence: 82%
“…Some adult TA patients showed dyslipidemia, which may be a risk factor for complicating atherosclerosis [22]. Also, dyslipidemia is suggestive of disease activity [23]. Here, dyslipidemia was identified in 60% (3/5) of cases, similar to that reported previously [22]; however, the disease activity scores for children with and without dyslipidemia were not statistically different.…”
Section: Discussionsupporting
confidence: 82%
“…In the majority of papers, patients with active disease presented with higher ESR and CRP levels as compared with patients with stable/inactive disease (ESR ranged 5–115 mm/hour vs 1–43 mm/hour and CRP ranged 0.1–99.1 mg/dL vs 0.06–7.77 mg/dL for active vs stable disease, respectively). Nevertheless, 28.5% of patients classified as being in remission (National Institutes of Health (NIH) criteria) may present with elevated CRP and 23.8% with elevated ESR23 (overall LoE 4) 23–29…”
Section: Resultsmentioning
confidence: 99%
“…In one case–control study (n=120), high-sensitivity CRP was a significant predictor of major cardiac events 30. Adding to cardiovascular risk, patients with TAK present a more atherogenic lipid profile when compared with healthy controls, but not when compared with coronary artery disease controls 26 30…”
Section: Resultsmentioning
confidence: 99%
“…Lipid metabolism disorders are related to the activity of TAK 14 . Inflammatory cytokines such as interleuken-6 and tumor necrosis factor-α can promote the LDL receptor-independent uptake of oxidized LDL.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of knowledge about aneurysm risk in TAK patients due to the rarity of the disease. Previous studies have found that prevalent of dyslipidemia in patients with TAK was 19–47% 1013 , and that lipids disorders are related to the activity of TAK 14 . The purpose of this study was to investigate the clinical and laboratory features of TAK and to analyze the combination of TAK and dyslipidemia as a risk factor for aneurysm formation.…”
Section: Introductionmentioning
confidence: 93%